La razionalità algoritmica. Elementi per una genealogia - De Stefano, Lorenzo (Mechane, 2025)
This article traces a genealogy of algorithmic rationality from ancient rituals to AI according to a theory of machine. It highlights how algorithms, as particular kind of pseudo-machine, shape and reflect humanity’s drive for order and control. From symbolic AI to neural networks, AI systems mirror cultural and political forces. The paper argues AI as particular kind of algorithmic machine isn’t neutral but tied to power and values, advocating for ethical governance and democratization to harness AI’s potential for societal good while acknowledging its deep historical roots in automation, cybernetics and decision-making.